„Ez a mi munkánk…” – A pedagógus ideális célja a magyar köznevelésben (Training and Practice : Journal of Educational Sciences, 2019)
No other profession is more important than that of a pedagogue. That is why it is important to increase the quality continuously. The initial point of it is to know where we are and to what extent we can be satisfied with our occupation’s result. Furthermore, we also have to examine in which direction we should develop. In the first part the study systematizes the accepted thesis on the topic. Afterwards, research, made by a metaphor research method, is introduced with the help of an online application (N=436) and its result. From this we can get to know the participants’ demands, especially those of the students in public education. We can learn what they think about the activities of the school, its meant and ideal aims and objectives. Finally, the paper drafts these aims and objectives in order to make the adequate steps towards improvement.